High-energy neutrinos from astrophysical accelerators of cosmic ray nuclei - Anchordoqui, L; Hooper, D; Sarkar, S; Taylor, A (2007)
Ongoing experimental efforts to detect cosmic sources of high energy neutrinos are guided by the expectation that astrophysical accelerators of cosmic ray protons would also generate neutrinos through interactions with ambient matter and/or photons. However there will be a reduction in the predicted neutrino flux if cosmic ray sources accelerate not only protons but also significant number of heavier nuclei, as is indicated by recent air shower data. We consider plausible extragalactic sources such as active galactic nuclei, gamma-ray bursts and starburst galaxies and demand consistency with the observed cosmic ray composition and energy spectrum at Earth after allowing for propagation through intergalactic radiation fields. This allows us to calculate the expected neutrino fluxes from the sources, normalised to the observed cosmic ray spectrum. We find that the likely signals are still within reach of next generation neutrino telescopes such as IceCube.